Real-world impact of glycated hemoglobin reduction on treatment intensification and glycated hemoglobin goal attainment in type 2 diabetes mellitus patients initiated on a sodium glucose co-transporter 2 (SGLT2) inhibitor (SGLT2i). (2nd September 2019) - Brunton, Stephen; Rozjabek, Heather M.; Pilon, Dominic; Lafeuille, Marie-Hélène; Kamstra, Rhiannon; Wynant, Willy; Bookhart, Brahim K.; Lefebvre, Patrick
Abstract: Objective: To evaluate the impact of a 0.2% reduction in glycated hemoglobin (HbA1c) on treatment intensification, poor HbA1c control and HbA1c goal attainment in patients with type 2 diabetes mellitus (T2DM) initiated on a sodium glucose co-transporter 2 (SGLT2) inhibitor (SGLT2i). Methods: IQVIATM Health Plan Claims Data – US and IQVIATM Ambulatory EMR Data – US databases (29 October 2012–31 March 2016) were used to identify adults with T2DM initiated on an SGLT2i (index date) who had HbA1c measurements pre- and post-index, and ≥6 months of eligibility pre-index (baseline). HbA1c change was defined as the difference between the first post-index and the last pre-index measurements. Cox regression models were used to assess treatment intensification, poor HbA1c control (i.e. HbA1c > 9%, among patients <9% at baseline) and goal attainment (HbA1c < 7%, <8%; among patients with HbA1c above goal at baseline) adjusting for HbA1c change and baseline characteristics. Patients were observed up to one year after the first HbA1c measurement or end of eligibility. Hazard ratios (HRs) and 95% confidence intervals (CIs) were reported. Results: A total of 938 patients (mean age 54.9, 42.5% female, mean HbA1c 8.5%) were selected. Following SGLT2i initiation, each 0.2% reduction in HbA1c levels was associated with a decreased risk of treatment intensification (HR [95% CI] = 0.90 [0.86–0.92]), a decreased likelihood of reaching HbA1c > 9% (HR [95% CI] = 0.85 [0.79–0.88]) and higher likelihoods of achieving a treatment goal of HbA1c < 7% (HR [95% CI] = 1.17 [1.12–1.21]) and HbA1c < 8% (HR [95% CI] = 1.08 [1.04–1.10]). Conclusions: In T2DM patients, each HbA1c reduction of 0.2% following the initiation of an SGLT2i was associated with a significant positive impact on treatment intensification and HbA1c goal attainment.